Antiliver Fibrosis Screening of Active Ingredients from Apium graveolens L. Seeds via GC-TOF-MS and UHPLC-MS/MS - Qiao, Ming (Evid Based Complement Alternat Med, 2020)
Although several studies have been performed on Apium graveolens L.(celery) seeds, their antiliver fibrosis effects remain to be unexplored. Firstly, we detected the effects of celery seeds extracted with different concentrations of aqueous ethanol on the proliferation of HSC-LX2 cells. Then, we detected the effects of fractions of the optimal effect extract on the proliferation and apoptosis of HSC-LX2 cells. Finally, the compounds of petroleum ether (PP), ethyl acetate (PE), n-butyl alcohol (PB), and water fractions (PW) of the optimal effect extract were determined by GC-TOF-MS and UHPLC-MS/MS, to confirm the potentially antifibrotic compounds combined with pharmacodynamic experiment of monomer compounds in vitro. The results revealed that 60% ethanol extract of celery seeds (60-extract) exhibited remarkable inhibition effect on the proliferation of HSC-LX2 cells compared with 95% ethanol and aqueous extract. Besides, it validated that the inhibition rates of PP, PE, PB, and PW on the proliferation of HSC-LX2 cells were 75.14%, 73.52%, 54.09%, and 43.36%, and their percentage of apoptotic cells were 37.5%, 4.3%, 0.7%, and 0.1% at high doses, respectively. Additionally, it was manifested that apigenin, aesculetin, and butylphthalide have major contribution to the overall compounds of celery seeds, and the inhibition effects on the cell proliferation clearly elevated with increase in their contents. In essence, apigenin, aesculetin, and butylphthalide may hopefully become the natural products of antiliver fibrosis, which laid a foundation for the subsequent development of celery seeds as antiliver fibrosis drugs.